A microscopy study of nickel-based superalloys performance in type I hot corrosion conditions - Waeytens, Manon; Syed, Adnan U.; Roberts, Tracey; Duarte Martinez, Fabian; Gray, Simon; Nicholls, John R. (Taylor & Francis, 2023)
Alloy material selection for sustainable, efficient, and cost-effective use in components is a key requirement for both power generation and aerospace sectors. Superalloys are manufactured using a combination of different elements, selected carefully to balance mechanical performance and environmental resistance to be used in a variety of different service conditions. Therefore, a fundamental understanding of each element is critical to alloy design. In this paper, the interaction of alloy chemistry, particularly chromium as a corrosion-resistant element along with titanium and molybdenum, and their effect on alloys performance for the relevant gas turbine industries were discussed. Based on the findings, the single-crystal alloy is found to be a better corrosion resistant alloy exhibited higher corrosion resistance in comparison to polycrystal alloys and proved that microstructure has a significant impact on alloy performance. This study also established that molybdenum level in chromia former alloys can significantly enhance the corrosion damage.
Keywords: type I hot corrosion; nickel alloy; chromium; corrosion resistance; scanning electron microscope; energy dispersive X-ray